Narrative self-recreation in virtual reality - Georgieva, Iva; Georgiev, Georgi V. (Frontiers in Virtual Reality, 2022)
The narrative essence of human nature is that humans are storytellers, and this ability helps to constitute our identities. Challenges that disrupt this innate ability are adverse events that affect the human perception of the world and undermine the meaning one finds in reality. Such events might range from short-term stressors to long-term testing conditions such as pandemics. Tools for overcoming these negative effects and for achieving self-preservation might be sought in individual storytelling abilities in relation to self-constitution and identification. An example of an interactive digital narrative medium that provides a platform for such expression of complex issues is virtual reality (VR), which has been used as a visual narrative storytelling tool for decades. This study sets the notion of trauma in a new light, as a break in the individual story used to explain one’s life and as a story to be intertwined with and re-adapted to one’s overall lifetime. In the healthcare context, this experience can be most effectively presented in VR because it offers added meaning, potential choices, closure, and resolution as methods of utilization. Therefore, VR can be seen not only as a medium whereby traumatic events can be processed but also as an alternative viewpoint of the goal of self-(re)creation. This research discusses a theoretical proposal for ways of playing with self-construction mechanisms in the context of an immersive VR environment to create more opportunities to change one’s narrative and, hence, one’s real-life story.